The Mystery of Waugh Syndrome: Unraveling a Rare Diagnostic and Surgical Enigma - Sanjay Dhungana; Jasmine Bajracharya; Kshitiz Kayastha; Bineet Thapa; Bipu Dhakal (Clinical Case Reports)
ABSTRACT Waugh Syndrome should be considered in a pediatric patient presenting with acute abdomen with features of intussusception, even when symptoms mimic acute gastroenteritis. Clinicians, particularly pediatric surgeons, must be aware of this condition for timely diagnosis and treatment to prevent the complications.